More Precise Control of the In Vitro Enzymatic Degradation via Ternary Self-Blending of High/Medium/Low Molecular Weight Poly(trimethylene carbonate) - Cai, Guiyang; Hou, Zhipeng; Li, Peng; Sun, Wei; Guo, Jing; Yang, Liqun; Yang, Qing (Frontiers in Materials, 2021)
To more precisely control the degradation rate of PTMC, PTMC self-blending films were prepared via the ternary self-blending of pure PTMC with molecular weight of 334, 152 and 57 kg/mol. The in vitro enzymatic degradation of the PTMC self-blending films was performed in lipase solutions. The results showed that the ternary self-blending could control the degradation of PTMC by adjusting the mass ratio of high/medium/low molecular weight PTMC in composition, and the PTMC334/PTMC152/PTMC57 films with a mass ratio of 1/4/16 showed a mass loss of 85.96% after 7 weeks degradation, while that of PTMC334/PTMC152/PTMC57 films with a mass ratio of 1/1/1 was 96.39%. The degradation rate constant of the former and the latter was 13.263 and 23.981%/w, respectively, and the former presented a better form-stability than the latter. The ternary self-blending could simultaneously bestow PTMC with lower degradation rate and good form-stability, indicating that ternary self-blending is an effective strategy to control the degradation of PTMC more precisely.